Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Sikap Etis Mahasiswa (Studi Kasus Pada Mahasiswa Program Studi Manajemen 2017 Universitas Islam Malang) - Moh. Rechal Sifaul Hamdani; Agus Widarko; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze the influence of intellectual intelligence, emotional intelligence and spiritual intelligence on students' ethical attitudes. The sampling method in this study used purposive sampling. The sample used in this study were management students of the 2017 Islamic University of Malang, the sample obtained was 84 respondents. The results of this study indicate that partially all variables have a significant and positive effect. While the results of multiple linear regression analysis showed a positive influence on students' ethical attitudes.Keywords: Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Student Ethical Attitude